Role of senataxin in R-loop-mediated neurodegeneration - Kannan, A; Gangadharan Leela, S; Branzei, D; Gangwani, L (Oxford University Press, 2024)
Senataxin is an RNA:DNA helicase that plays an important role in the resolution of RNA:DNA hybrids (R-loops) formed during transcription. R-loops are involved in the regulation of biological processes such as immunoglobulin class switching, gene expression and DNA repair. Excessive accumulation of R-loops results in DNA damage and loss of genomic integrity. Senataxin is critical for maintaining optimal levels of R-loops to prevent DNA damage and acts as a genome guardian. Within the nucleus, senataxin interacts with various RNA processing factors and DNA damage response and repair proteins. Senataxin interactors include survival motor neuron and zinc finger protein 1, with whom it co-localizes in sub-nuclear bodies. Despite its ubiquitous expression, mutations in senataxin specifically affect neurons and result in distinct neurodegenerative diseases such as amyotrophic lateral sclerosis type 4 and ataxia with oculomotor apraxia type 2, which are attributed to the gain-of-function and the loss-of-function mutations in senataxin, respectively. In addition, low levels of senataxin (loss-of-function) in spinal muscular atrophy result in the accumulation of R-loops causing DNA damage and motor neuron degeneration. Senataxin may play multiple functions in diverse cellular processes; however, its emerging role in R-loop resolution and maintenance of genomic integrity is gaining attention in the field of neurodegenerative diseases. In this review, we highlight the role of senataxin in R-loop resolution and its potential as a therapeutic target to treat neurodegenerative diseases.